2008
DOI: 10.1007/s00125-008-1038-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically healthy but obese women: effect of an energy-restricted diet

Abstract: Abbreviations FFM fat-free mass FM fat mass MHO metabolically healthy but obese To the Editor: A unique subset of obese individuals has been identified that appears to be protected against obesityrelated metabolic disturbances [1,2]. These individuals, now known as 'metabolically healthy but obese' (MHO) individuals, display a favourable metabolic profile, characterised by high levels of insulin sensitivity, normal lipid and inflammation profiles and no sign of hypertension, despite having excessive body fatne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
115
0
15

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 7 publications
15
115
0
15
Order By: Relevance
“…46 In addition, CR has been shown to significantly improve IS in previously obese, diabetic subjects. 2,47 Coming from a pathological state of IR, which might be comparable to the acute OF in the present study, CR thus seems to have favorable effects on glucose metabolism.…”
Section: Discussionsupporting
confidence: 56%
“…46 In addition, CR has been shown to significantly improve IS in previously obese, diabetic subjects. 2,47 Coming from a pathological state of IR, which might be comparable to the acute OF in the present study, CR thus seems to have favorable effects on glucose metabolism.…”
Section: Discussionsupporting
confidence: 56%
“…In conclusion, the study by Karelis et al [9] confirms the effectiveness of an energy-restricted diet for improving whole body insulin sensitivity in association with small reductions in body fat. Interestingly, it also shows that there is a subset of individuals, the most insulin sensitive, that is non-responsive to this treatment and may potentially have a detrimental response.…”
mentioning
confidence: 59%
“…With respect to the clinical relevance of metabolically healthy but obese women, in this issue of Diabetologia, Karelis et al [9] report the original finding that these women may respond differently to an energy-restricted diet than insulin-resistant obese women. From an original population of 121 obese women recruited for a weight loss programme, the authors present data on two selected subgroups of women: those within the upper quartile (the metabolically healthy but obese postmenopausal women) and those within the lower quartile (insulin-resistant and 'at-risk' individuals) of insulin sensitivity values as assessed by means of the euglycaemic-hyperinsulinaemic clamp.…”
mentioning
confidence: 99%
“…Data about the effects of lifestyle modifications specifically in MHO and OIR populations are sparse: two small studies implemented energy-restriction diets for 12 weeks and 6 months in women [8,9], and one a 6 month exercise intervention programme, also in women [10]. All three studies showed an improvement in cardiovascular risk profile in OIR, but not in MHO, women, despite similar weight loss [8][9][10]. In view of these findings and the limited healthcare resources, the necessity and the benefit of a lifestyle intervention in MHO individuals has been questioned [11,12].…”
Section: Introductionmentioning
confidence: 99%